Knowledge and counseling skills of Accredited Social Health Activists on Infant and Young Child Feeding: A community-based study in a rural block of West Bengal, India - Aprajita Jha; Pramit Goswami; Sutapa Mandal; Pranita Taraphdar; Arif Hossain; Suman Sannigrahi (Asian Journal of Medical Sciences, 2024)
Background: Nutrition is critical to the health and development of infants and children. Nutritional deficiencies in early life result in long-term impairment in growth. Optimal infant and young child feeding (IYCF) practices are one of the most effective interventions in improving child health. Aims and Objectives: The study was conducted to assess the knowledge and counseling skills of Accredited Social Health Activists (ASHAs) regarding IYCF in Bhatar community development block of Purba Bardhaman District. Materials and Methods: A descriptive and cross-sectional study was conducted among 110 study subjects selected randomly from 17 subcenters and 38 health and wellness centers of Bhatar block of Purba Bardhaman District. It was conducted using a pre-designed, pre-tested schedule having a total score of 16, from November 2023 to February 2024. Results: Mean knowledge score of ASHAs regarding IYCF was 12.05±2.24. On further analysis, good, average, and poor knowledge about IYCF was observed among 9.1%, 78.2%, and 12.7% of the ASHA workers, respectively. On univariate analysis, level of knowledge was found to be significantly associated with duration of service (P=0.001) and training status (P=0.00) of ASHAs. It was observed that messages regarding the addition of oil/ghee and proper hand washing after handling child’s excreta were mostly missed during counseling sessions. Conclusions: Most ASHA workers had correct knowledge on IYCF but during counseling sessions, most of the key messages were not provided by them to mothers. Thus, it was concluded that a change in training approach is necessary for enhancing counseling skills and knowledge-sharing by ASHAs.